Wykorzystanie możliwości serwisu YouTube przez Rodzimy Kościół Polski w budowaniu społeczności wirtualnej - Daraż-Duda, Katarzyna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
Native Polish Church uses its YouTube channel - Rodzimy Kościół Polski RKP.ORG.PL - primarily as a space for sharing niche content, addressed to a specific group of recipients (native believers and people interested in Slavic Native Faith). YouTube is not recognised by the church as a space where an online community should, or can, be formed that would be willing to take collective action, whether in the online space or beyond. Restricting opportunities for interaction, by limiting the options for commenting on published material, is convenient from the perspective of the channel owners, as it does not require them to familiarise themselves with and moderate immediate feedback from YouTube users. However, the preferred style of communicating, from broadcaster to viewer, does not mean that the founder of the channel does not understand the principles of media activity on YouTube. Quite the contrary. Contemporary YouTube is not only about video, but also about podcasts, which - despite the fact that they “originated from radio” - successfully function in a platform that is so often defined, among other things, as a service for sharing and archiving audio-visual materials.